Prevalence of high blood pressure in children and adolescents. Influence of obesity. - de Macedo, M. (2019)
Obesity is associated with high blood pressure BP, mainly in adults. It has been suggested that body fat patterning plays a role in the etiology of hypertension. This relationship also exists in children, however it is less well known. The aim of this study was to evaluate the prevalence of high blood pressure (HBP) in children and adolescents, and the influence of obesity on this population, as well as the presence of familial aggregation for these factors. Eight hundred and eighty-nine children (389 boys and 500 girls aged 5-18 years) and their parents, from the North of Portugal were studied. Systolic blood pressure, diastolic blood pressure, weight, height, triceps skinfold, body mass index and sexual maturation were measured. The criterion of high blood pressure was defined as the BP being higher than the 90th percentile. All variables were converted to age and sex in specific "Z-scores". A SPSS package was used. We found 47 (5.2%) people of both sexes to have high blood pressure. The children of this group were compared with the normotensive group. These children were heavier (p < 0.005) and more obese (p < 0.0001) than the others. No difference was found for sexual maturation or height. The parents of the group with high blood pressure were heavier (p < 0.001) and more obese (p < 0.01) than the parents of the normotensive group. In conclusion, obesity is an important factor in children with higher values. Children with HBP are more likely to come from families with history of obesity. The identification of these risk factors in children is an important contribution to the prevention of cardiovascular disease in adulthood.